Enhanced mPGES-1 Contributes to PD-Related Peritoneal Fibrosis via Activation of the NLRP3 Inflammasome - Luo, Qimei; Hu, Qinghua; Zheng, Qingkun; Gong, Lewei; Su, Lijuan; Ren, Baojun; Ju, Yongle; Jia, Zhanjun; Dou, Xianrui (Frontiers in Medicine, 2021)
Background: Microsomal prostaglandin E synthase-1 (mPGES-1)-derived prostaglandin E2 (PGE2) is a chief mediator of inflammation. However, the role and mechanism of mPGES-1 in peritoneal dialysis (PD)-associated peritoneal fibrosis have not been investigated. Material and methods: In PD patients, mPGES-1 expression in peritoneum tissues and the levels of PGE2, IL-1β and IL-18 in the dialysate were examined. In rat peritoneal mesothelial cells (RPMCs), the regulation and function of mPGES-1 and NLRP3 inflammasome were investigated. The expression of extracellular matrix proteins and the components of NLRP3 inflammasome were detected by Western blotting or real-time quantitative PCR. Results: In PD patients with ultrafiltration failure (UFF), mPGES-1 was enhanced in the peritoneum, which was associated with the degree of peritoneal fibrosis. Accordingly, the intraperitoneal PGE2 levels were also positively related to the PD duration, serum C-reactive protein levels, and serum creatinine levels in incident PD patients. In RPMCs, high-glucose treatment significantly induced mPGES-1 expression and PGE2 secretion without affecting the expressions of mPGES-2 and cPGES. Inhibition of mPGES-1 via short hairpin RNA significantly ameliorated the expression of extracellular matrix proteins of RPMCs induced by high glucose. Additionally, high glucose markedly activated NLRP3 inflammasome in RPMCs that was blunted by mPGES-1 inhibition. Furthermore, silencing NLRP3 with siRNA significantly abrogated the expression of extracellular matrix proteins in RPMCs treated with high glucose. Finally, we observed increased IL-1β and IL-18 levels in the dialysate of incident PD patients, showing a positive correlation with PGE2. Conclusion: These data demonstrate that mPGES-1-derived PGE2 plays a critical role in PD-associated peritoneal fibrosis through activation of the NLRP3 inflammasome. Targeting mPGES-1 may offer a novel strategy to treat peritoneal fibrosis during PD.